2018
DOI: 10.1038/s41427-018-0024-7
|View full text |Cite|
|
Sign up to set email alerts
|

Naked-eye point-of-care testing platform based on a pH-responsive superwetting surface: toward the non-invasive detection of glucose

Abstract: Herein, we demonstrate a contact angle (CA)-based naked-eye point-of-care testing platform with rapid pH-responsive superwettability that can switch between superhydrophilic and superhydrophobic properties for quantitative biosensing. The CA of the droplet on the pH-responsive surface approached~0°at pH 1 and conversely reached 161.4°± 6.2°at pH 13. We realized the sensitive detection of the pH, urea, and glucose by monitoring the changes in the CA. The traditional invasive diagnosis of diabetes causes pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…4 However, organic compounds with molecular masses of less than 500 Da, such as PPD, have been shown to easily cross the skin barrier and are regarded as human allergens and carcinogens. 5 To address this issue, some nontoxic nanomaterials, which are versatile in biomedical, [6][7][8] nano-engineering, 9,10 and clean energy 11,12 applications, have also been developed as safe dyeing agents. For example, Huang and coworkers found that graphene-based hair dyes could greatly shorten the dyeing time and improve antistatic performance.…”
mentioning
confidence: 99%
“…4 However, organic compounds with molecular masses of less than 500 Da, such as PPD, have been shown to easily cross the skin barrier and are regarded as human allergens and carcinogens. 5 To address this issue, some nontoxic nanomaterials, which are versatile in biomedical, [6][7][8] nano-engineering, 9,10 and clean energy 11,12 applications, have also been developed as safe dyeing agents. For example, Huang and coworkers found that graphene-based hair dyes could greatly shorten the dyeing time and improve antistatic performance.…”
mentioning
confidence: 99%
“…Subsequently, in 2017, their group reported another electrochemical biosensor based on a novel stimuli‐responsive copolymer, 137 which was applied for selectively and sensitively detecting sialic acid (SA) in mouse brain. Our group reported an effective point‐of‐care testing (POCT) device based on pH‐responsive superwettable surfaces (Figure 10A), 138 which were prepared by modifying silica nanoparticles with the organosilanes (3‐[2‐(2‐amino ethylamino) ethylamino] propyl trimethoxy silane (AEPTMS) and octyl trimethoxy silane (OTMS)). Because of the switch between superhydrophobicity and superhydrophilicity, pH, urea, and glucose were specifically detected just by naked‐eye.…”
Section: Bioinspired Superwetting Surfaces For Biosensingmentioning
confidence: 99%
“…(D) Non‐invasive detection of saliva and urine obtained from nine patients with diabetes and six normal people illustrating that the CA can be employed to distinguish between samples of people with diabetes and normal people. Reproduced with permission 138 . Copyright 2018, Nature Publishing Group…”
Section: Bioinspired Superwetting Surfaces For Biosensingmentioning
confidence: 99%
“…An acidic environment results in the protonation of the amino groups, which makes the surfaces very hydrophilic, while an alkali condition changes the surfaces into a very hydrophobic state. With this surface, the level of glucose in the saliva and urine can be accurately measured in one second by recording the contact angle of the liquid sample, based on the produced gluconic acid after the addition of glucose oxidase in the sample [83]. This non-invasive, low-cost, rapid glucose detection method is beneficial to overcome the limitations of the traditional invasive diagnosis of diabetes such as pain and infection risk.…”
Section: Diagnosticsmentioning
confidence: 99%